2021
DOI: 10.2217/bmm-2021-0271
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-To-Lymphocyte Ratio Is Prognostic in Recurrent Glioblastoma Multiforme Treated with Bevacizumab Plus Irinotecan

Abstract: Aim: We intended to survey the prognostic utility of pretreatment neutrophil-to-lymphocyte ratio (NLR) as a novel prognostic index in recurrent glioblastoma multiforme (R-GBMs) treated with bevacizumab plus irinotecan (BEVIRI). Patients & methods: The present retrospective investigation incorporated the R-GBMs patients who underwent BEVIRI. The pre-BEVIRI NLR was calculated for each patient by utilizing the complete blood count tests obtained on the first day of BEVIRI. Results: The data of a total of 103 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Regarding the state of the systemic immune response in recent years, the scientific literature has accumulated much data on the importance of preoperative NLR for patient survival, with some authors reporting statistical significance not only for survival in GBM but also for tumor grade and as a distinguisher from CNS metastasis (Table 1 ) [ 10 - 12 , 20 - 27 ]. Interesting additional data from these studies are those of Weng and Kemerdere, where a positive correlation was found between the rate of increase in NLR and the histological grade of tumors, as well as data from Haksoyler, who proved that the prognostic value of the index is preserved even in disease recurrence [ 21 , 24 , 26 ]. One contradictory but promising result is the reported elevation of NLR by Figueroa in GBM patients undergoing laser interstitial thermal therapy, where the patients are reported to have a better outcome [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the state of the systemic immune response in recent years, the scientific literature has accumulated much data on the importance of preoperative NLR for patient survival, with some authors reporting statistical significance not only for survival in GBM but also for tumor grade and as a distinguisher from CNS metastasis (Table 1 ) [ 10 - 12 , 20 - 27 ]. Interesting additional data from these studies are those of Weng and Kemerdere, where a positive correlation was found between the rate of increase in NLR and the histological grade of tumors, as well as data from Haksoyler, who proved that the prognostic value of the index is preserved even in disease recurrence [ 21 , 24 , 26 ]. One contradictory but promising result is the reported elevation of NLR by Figueroa in GBM patients undergoing laser interstitial thermal therapy, where the patients are reported to have a better outcome [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Index has been extensively studied in other CNS tumors. The recent studies suggest that NLR may be a novel biomarker for the prognostic stratification of R-GBMS treated with BEVIRI (23). Another study conducted by Dr. Erkan Topkan (24) showed that preconditioning pretreatment systemic immune response index (SIRI) is a new, reliable, and independent predictor of prognosis for newly diagnosed patients with GBM intending to undergo postoperative Stupp regiments.…”
Section: Discussionmentioning
confidence: 99%
“…A vicious circle is created. Upon activation, these cells are responsible for the secretion of a substantial number of inflammatory factors: cytokines, matrix metalloproteinases—MMP, growth and oxidative stress factors, that next will suppress or activate the signaling pathways, modifying their beneficial tissular action and promoting tumor development and invasion [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%